Fostering religious moderation in the digital age: A study of community intervention through TikTok - Annisa Fitriani; Yusafrida Rasyidin; Yoga Irawan (INSPIRA: Indonesian Journal of Psychological Research, 2025)
The social media platform TikTok, widely popular among younger demographics, offers diverse content, including educational material. Such content can foster public understanding of religious moderation. This study aims to evaluate the effectiveness of social media, specifically the TikTok account @Tanya_SIMO, as a community intervention to cultivate religiously moderate behavior. The sample consisted of 66 followers of the @Tanya_SIMO account who participated in the intervention from start to finish, selected via simple random sampling. Descriptive analysis revealed that the post-test mean score was higher than the pre-test mean score, suggesting a positive influence from the @Tanya_SIMO videos. This was confirmed by a paired-samples t-test, which yielded a significant change index (t = -3.809) and a p-value of < .001. The pre-test mean was 4.88, which increased to 5.39 after participants viewed the videos, indicating enhanced comprehension of religious moderation among followers. These findings confirm the effectiveness of the @Tanya_SIMO TikTok account as a platform for educating its audience on religious moderation.